The Association between Adolescent's Weight Perception and Health Behaviors: Analysis of National Health and Nutrition Examination Survey Data, 2011-2014 - Furong Xu; Mary L. Greaney; Steven A. Cohen; Deborah Riebe; Geoffrey W. Greene (Hindawi Limited, 2018)
The association between adolescents' weight perception and their physical activity (PA) and sedentary behaviors remains unclear. Therefore, these associations were explored using data from 2438 adolescents aged 12-19 years who participated in the National Health and Nutrition Examination 2011-2014 Survey. Respondents reported weight perception, and their weight perception accuracy was determined by examining whether the measured weight and perceived weight were concordant. Respondents also reported sedentary time (sitting time and screen time), PA, and intention to lose weight. Linear and logistic regression models were conducted to determine whether adolescents' PA, sedentary behaviors, and weight loss intention differed by weight perception and weight perception accuracy adjusted for demographic variables accounting for complex sampling. About one-quarter (21.4%) of the respondents had obesity. For respondents who perceived themselves as being overweight/fat, despite greater weight loss intention, males reported more sitting time (512.7 ± 16.3 versus 474.1 ± 10.2 minutes/day, p<0.05) and females reported less PA (48.7 ± 5.0 versus 64.6 ± 3.3 minutes/day, p<0.05) than respondents who perceived themselves as being normal weight. Similar patterns were observed for weight perception accuracy among individuals with obesity. Study results show that perceiving oneself as being overweight/fat regardless of accuracy was associated with more sedentary time for males or less PA for females despite higher weight loss intention.